HUBUNGAN ANTARA SOKONGAN SOSIAL DENGAN KESUNYIAN DALAM KALANGAN WARGA EMAS BLOK 5 DI PPR SERI ALAM, KUALA LUMPUR - Razman, Nur Afiqah; Shaban, Siti Haziqah (Jurnal 'Ulwan, 2023)
The elderly are those who are face disabilities, loneliness and face health problem in term of physical and mental health. Social support is needed by the elderly to live their daily lives but it may vary according to the gender and employment status of the elderly. The aim of this study was to examine the relationship between social support and loneliness among senior citizen block 5 PPR Seri Alam, Kuala Lumpur. A set of questionnaires consisting of three parts was used which is the respondent’s demography, Socially Supportive Behaviour questionnaires to measure social support and UCLA Loneliness Scale to measure loneliness. Survey design and simple random sampling technique were chosen in conducting this study. The result of this research analysis included descriptive statistics based on correlation method, t-test and Anova. A total of 60 respondents were chosen as the samples for the survey design. The result showed that there was significant relationship between social support and loneliness among senior citizens [r= .796, k < .05]. Besides that, the result also indicated that there was no significant difference in social support based on employment status [F (2, 57) = 1.447, k > .05]. Next, there also was significant difference in social support based on gender [t (58) = 0.016, k > .05]. In conclusion, this study is to see the extent to which social support affects the loneliness elderly at Block 5 PPR Seri Alam.